Comprehensive analyses of plant hormones in etiolated pea and maize seedlings grown under microgravity conditions in space: Relevance to the International Space Station experiment "Auxin Transport". (February 2023) - Yamazaki, Chiaki; Yamazaki, Tomokazu; Kojima, Mikiko; Takebayashi, Yumiko; Sakakibara, Hitoshi; Uheda, Eiji; Oka, Mariko; Kamada, Motoshi; Shimazu, Toru; Kasahara, Haruo; Sano, Hiromi; Suzuki, Tomomi; et al.
Abstract: Functional relationships between endogenous levels of plant hormones in the growth and development of shoots in etiolated Alaska pea and etiolated Golden Cross Bantam maize seedlings under different gravities were investigated in the "Auxin Transport" experiment aboard the International Space Station (ISS). Comprehensive analyses of 31 species of plant hormones of pea and maize seedlings grown under microgravity (μ g ) in space and 1 g conditions were conducted. Principal component analysis (PCA) and a multiple regression analysis with the dataset from the plant hormone analysis of the etiolated pea seedlings grown under μ g and 1 g conditions in the presence and absence of 2, 3, 5-triiodobenzoic acid (TIBA) revealed endogenous levels of auxin correlated positively with bending and length of epicotyls. Endogenous cytokinins correlated negatively with them. These results suggest an interaction of auxin and cytokinins in automorphogenesis and growth inhibition of etiolated Alaska pea epicotyls grown under μ g conditions in space. Less polar auxin transport with reduced endogenous levels of auxin increased endogenous levels of cytokinins, resulting in changing the growth direction of epicotyls and inhibiting growth. On the other hand, almost no close relationship between endogenous plant hormone levels and growth and development in etiolated maize seedlings grown was observed under μ g conditions in space, as per Schulze et al. (1992). However, endogenous levels of IAA in the seedlings grown under μ g conditions in space were significantly higher than those grown on Earth, similar to the cases of polar auxin transport already reported.